The Effect of Suweg (Amorphophallus paeoniifolius) Flour Substitution and Variation of Yeast Concentration on Chemical and Sensory Properties of Donuts - Maharani, Alifia; Irvia Resti Puyanda; Vivi Nuraini (Journal of Food and Agricultural Product, 2024)
Donuts are a type of bakery product made from high-protein wheat flour and have a distinctive shape, in the center is hollowed out like a ring. The purpose of this study was to determine the chemical and organoleptic characteristics of donuts with the addition of suweg flour and variations in yeast concentration that are most favored by consumers. This study used a factorial completely randomized design (CRD) with 2 factors, namely the ratio of wheat flour and suweg flour (90:10, 85:15, and 80:20) and variations in yeast concentration (2, 4, and 6%). The best donut formulation favored by panelists was the formulation of 85% wheat flour: 15% suweg flour and the addition of 4% yeast concentration, where the donuts have a liking value for color 3.96 (neutral), taste 3.48 (neutral), aroma 3.00 (neutral), texture 3.88 (neutral), and overall liking 3.80 (neutral), and have a moisture content of 19.75%, ash content 1.01%, fat content 28.00%, total protein content 8.13%, carbohydrate content 43.11%, and crude fiber content 6.32%. Therefore, based on the results of the study, the formulation chosen was the formulation of 85% wheat flour: 15% suweg flour and the addition of 4% yeast concentration.